Methods Of Instrumental Treatment of Root Canals (Texas Journal of Medical Science, 2021)
In order to eliminate the shortcomings of instrumental processing when using the deviation technique, it has been modified. What is the difference between the modern methodologies? Channel processing is started in the same way as with the traditional method, but after using file No. 25, the apical third of the channel is once again processed to larger files that are better suited for adequate channel cleaning